Socio-religious harmony index instrument indicators for Malaysia - Abdullah, Muhammad Ridhuan Tony Lim; Endut, Mohd Nuri Al-Amin; Ahmad Yusoff, Atifah; Baharuddin, Azizan; Abdul Khir, Mohd Faizal; Talib, Ahamad Tarmizi (Jabatan Sejarah dan Tamadun Islam, Universiti Malaya, 2016)
The subject of inter-religious relationship among different religious adherents is crucial in determining social peace and harmony in a multi religious country like Malaysia. The question to what extend the society is susceptible to religious issues remains uncertain. This study will contribute in understanding the Malaysian socio-religious harmony status among the multi-religious adherents through development of the social religious index. To suffice part of this effort, the aim of this study was to develop the socio-religious harmony index instrument which is viable to measure socio-religious harmony level in Malaysia. However, the development of a reliable and valid instrument relies heavily on the quality of the variables or the indicators to be used to measure the index. Hence, the instrument was developed using key informants’ input via experts’ panelist which included selected stakeholders from various backgrounds such as academics, ministry officers, policy makers, non-government organization members, and head or representative of religious groups. To effectively manage the input from the expert panelists, the study adopted Fuzzy Delphi Method (FDM) as main methodology to determine the indicators and sub-indicators (quantitative indicators) to be included in the index instrument questionnaires. Fuzzy Delphi was conducted in two rounds: FDM round 1 to determine the main indicators and FDM 2 to determine the sub-indicators to measure each main indicators. Based on the experts’ consensus, the findings of FDM 1 proposed 22 socio-religious harmony indicators. For FDM 2, based on the indicators, the experts proposed 53 sub-indicators as quantitative indicators to measure each indicators. These indicators and their respective sub-indicators will be used to form the index instrument.